Predicting intentions to meet fruit & vegetable recommendations among black emerging adult women. Issue 3 (3rd April 2022) - Kelly, Terri-Ann; Kral, Tanja V.E.; Teitelman, Anne M.; Deatrick, Janet A.; Lewis, Lisa M.
Abstract: Objective To examine Black emerging adult women's (ages 18–29) intention to meet the recommended daily intake of fruits and vegetables using the Theory of Planned Behavior (TPB). Participants: Black emerging adult women (BEAW; N = 100). Methods: A cross-sectional survey design. Results: Hierarchical regression analyses revealed that in Model 1, attitudes ( p <.0001) and subjective norms ( p <.05) were significant predictors of intentions to meet the recommended daily intake of fruits and vegetables. In Model 2, attitudes ( p =.0001) and perceived behavioral control ( p <.0001) were revealed to be significant predictors of intentions. The change in R squared from Model 1 (R2=.304) and Model 2 (R2=.559), was 0.255 (F = 40.08, p <.0001) with the addition of perceived behavioral control to the second model. Conclusion: The TPB may be a suitable framework to assess factors associated with fruit and vegetable intentions among BEAW. Interventions designed to increase fruit and vegetable intake in BEAW should prioritize modifying perceived behavioral control.